2022
DOI: 10.1108/bfj-03-2021-0293
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic framework for sustainable open innovation in the food industry

Abstract: PurposeThis study aims to take a holistic perspective to investigate how open innovation supports sustainability and the contribution to the Unite Nations (UN) Sustainable Development Goals (SDGs).Design/methodology/approachThe study is based on an in-depth single case study of Andriani SpA, a leading Italian company in the food industry. The case is built by triangulating data from direct observations, documentary analysis and semi-structured interviews.FindingsThe findings show an organization that has devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 73 publications
(151 reference statements)
0
22
0
Order By: Relevance
“…Specifically, open innovation involves the acquisition and transfer of knowledge and technology (Kraus et al , 2020). After almost 20 years of research, a growing body of literature suggests that opening up to external knowledge sources both widely and deeply helps improve firm performance and build competitive advantages (Santoro et al , 2020; Venturelli et al , 2022).…”
Section: Business Model Innovation and Open Innovationmentioning
confidence: 99%
“…Specifically, open innovation involves the acquisition and transfer of knowledge and technology (Kraus et al , 2020). After almost 20 years of research, a growing body of literature suggests that opening up to external knowledge sources both widely and deeply helps improve firm performance and build competitive advantages (Santoro et al , 2020; Venturelli et al , 2022).…”
Section: Business Model Innovation and Open Innovationmentioning
confidence: 99%
“…Considering the previous studies and the existing literature, as evidenced in section 2 (Adams et al, 2016;Arcese et al, 2015;Bigliardi & Filippelli, 2022;Bogers et al, 2020;Costa & Matias, 2020;Gyamfi & Sein, 2021;Melane-Lavado & Álvarez-Herranz, 2020;Pizzi et al, 2020;Rauter et al, 2017;Rauter et al, 2018;Roszkowska-Menkes, 2018;Venturelli et al, 2022) and with the aim of deepening and specifying the analysis of the Enel case by focusing attention on the dynamics related to skill transfer (mediator) shown in the model developed in section 4, it is possible to conceive a representation (Table 6) of the strategic Open Innovation approach adopted by Enel.…”
Section: Discussion: Developing the Skin (Skills And Knowledge Improv...mentioning
confidence: 99%
“…However, previous studies (Venturelli et al, 2022) confirmed that the role of Open Innovation to facilitate and accelerate the process toward sustainable strategies could be relevant (Bogers et al, 2020; Rupo et al, 2018). There are a few studies in this sense and the present work is contextualized in this stream of literature.…”
Section: Introductionmentioning
confidence: 97%
“…This brings the OI paradigm and associated methodologies and practices to center stage in agri-food organizations' efforts to contribute to achieve a more sustainable future. In these issues, Venturelli et al (2022) illustrate how SMEs can strategically engage with the SDGs in the context of the food industry, and we content that studying how the OI paradigm can contribute to reaching the SDGs will probably be the most urgent OI research agenda for many years ahead. Advancing this agenda is challenging and will require research addressing all organizational and societal levels involved in the argifood industry.…”
Section: The Future Direction Of Oi Research In the Agri-food Industrymentioning
confidence: 99%
“…Moreover, as highlighted Misra and Mention (2022), the agri-food industry comprises complex value chains and networks consisting of input, production, processing and output stages. Of the eight articles in this special issues, one study addresses the intra-organizational level (Palumbo et al , 2022), and five studies mainly address the organizational level (Buallay, 2021; Dias et al , 2022; Rialti et al , 2022; Penco et al , 2022; Venturelli et al , 2022). The bias toward the organizational and inter-organizational level of analysis seems to mirror the general focus of agri-food industry OI-oriented research.…”
Section: The Future Direction Of Oi Research In the Agri-food Industrymentioning
confidence: 99%